Evaluation of Dental Trauma Knowledge Levels of Cyclists in Turkiye - Fatma Tunç; Emre Çulha (Selcuk Dental Journal)
Background: Cycling is a risky sport in terms of dental injury. Immediate treatment of traumatized teeth is very critical for the prognosis. This study aims to evaluate the knowledge levels and attitudes of cyclists in Turkey about dental trauma and its emergency treatment. Methods: In the study, a total of 12 questions were asked in the online questionnaire directed to the participants in different cities in Turkey. The answers received were divided into three groups according to their cycling experience; Group 1: less than 5 years, Group 2: 6-10 years, and Group 3: more than 11 years, and evaluated with the Chi-square and Bonferroni multiple comparison tests. P value < 0.05 was accepted as statistically significant. Results: According to the data obtained; It was determined that 31.8% of the participants in Group 3 and 10.4% of the participants in Group 2 did not use protective equipment while cycling (P